2021
DOI: 10.21203/rs.3.rs-900426/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

D-Dimer is a Predictive Factor of Cancer Therapeutics-Related Cardiac Dysfunction in Patients Treated With Cardiotoxic Chemotherapy

Abstract: Background: D-dimer is a sensitive biomarker for cancer-associated thrombosis, but little is known about its significance on cancer therapeutics-related cardiac dysfunction (CTRCD). Methods: Consecutive 169 patients planned for cardiotoxic chemotherapy were enrolled and followed up for 12 months. All patients underwent echocardiography and blood test at baseline, as well as at 3-month, 6-month, and 12-month. Results: The patients were divided into 2 groups based on the level of D-dimer (> 1.65 µg/ml or ≦ 1.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Plasma D-dimer, the smallest cross-linked protein produced in the proteolytic process, is a marker for detecting malignancy and is of great significance for the clinical exclusion of tumor-related thrombosis (21). Previous studies have shown the predictive role of plasma D-dimer in many malignancies treated with chemotherapy, including lung cancer (22)(23)(24)(25)(26), colorectal cancer (27), gallbladder carcinoma (20), and breast cancer (28). However, whether pretreatment D-dimer can predict therapeutic efficacy and prognosis in advanced NSCLC patients receiving ICI treatment remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma D-dimer, the smallest cross-linked protein produced in the proteolytic process, is a marker for detecting malignancy and is of great significance for the clinical exclusion of tumor-related thrombosis (21). Previous studies have shown the predictive role of plasma D-dimer in many malignancies treated with chemotherapy, including lung cancer (22)(23)(24)(25)(26), colorectal cancer (27), gallbladder carcinoma (20), and breast cancer (28). However, whether pretreatment D-dimer can predict therapeutic efficacy and prognosis in advanced NSCLC patients receiving ICI treatment remains unclear.…”
Section: Introductionmentioning
confidence: 99%